Nutritional and Functional Benefits of Cactus Fruit (Opuntia spp.) Bioactives: Implications for Edible Coating Applications (Development Engineering Conferences Center Articles Database, 2025)
The cactus fruit (Opuntia spp.), commonly known as prickly pear, is a globally recognized source of valuable nutrients and bioactive compounds. This review consolidates recent scientific literature (2018–2024) to elucidate the comprehensive nutritional profile and functional properties of cactus fruit. It is particularly rich in dietary fiber, essential vitamins, minerals, and a diverse array of phytochemicals, including betalains, flavonoids, and phenolic acids. These bioactives confer significant health-promoting attributes, with documented benefits spanning cardiovascular health, modulation of glycemic response, digestive system regulation, potent antioxidant and anti-inflammatory activities, positive effects on dermal health, and robust immune system support. Beyond its direct consumption benefits, this review explores the promising potential of incorporating cactus fruit bioactives into edible coatings. Such applications aim to enhance the preservation of foods, extend their shelf-life, and simultaneously deliver added health benefits to consumers. The discussion delves into the underlying mechanistic insights supported by evidence from scientific literature, complemented by detailed tables presenting compositional data and bioactivity profiles.